EVALUASI KEBIJAKAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) DALAM PENYELENGGARAAN LAYANAN AKADEMIK DI INSTITUT PEMERINTAHAN DALAM NEGERI KAMPUS NUSA TENGGARA BARAT - Finalia Putri; Fanila Kasmita Kusuma (Journal of Innovation Research and Knowledge, 2026)
The implementation of the Electronic-Based Government System (SPBE) in governmental educational institutions serves as a strategic step toward efficient, transparent, and accountable governance. The Institut Pemerintahan Dalam Negeri (IPDN) Nusa Tenggara Barat Campus, a government-affiliated university under the Ministry of Home Affairs, has implemented SPBE policy in its academic service delivery. This study aims to evaluate the SPBE policy in academic services at IPDN NTB Campus using William N. Dunn's (2003) six policy evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with nine informants, observation, and documentary analysis. Data analysis used the interactive model of Miles, Huberman, and Saldana (2014), with data validity ensured through source and method triangulation. Results show that SPBE policy implementation at IPDN NTB Campus has had a positive impact on digital-based academic service effectiveness, particularly through the Sistem Informasi Akademik dan Pelayanan (SIAP). However, challenges remain in ICT infrastructure efficiency, system feature adequacy, human resource capacity, and responsiveness mechanisms. This study recommends strengthening digital capacity of staff, improving network infrastructure, and establishing a structured periodic evaluation mechanism for SPBE implementation within IPDN.